Teachers’ Job Satisfaction: Findings from TALIS 2013 Study - Geske, Andrejs; Ozola, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper examines teachers’ satisfaction with their profession and work environment in relation to other environmental factors in schools. Latvian data from the OECD TALIS 2013 study are used in the data analysis. The aim of the study was to find out whether there is any relationship between teacher satisfaction with their work environment and profession and a varietyofvariablescharacterizingschoolsandstudents. The research question is: what are the most important factors associated with teachers' satisfaction with their job at school? Applied research methods are frequency analysis and measures of central tendency. The results of the research reveal that overall Latvian teachers are satisfied with their work environment, and teachers' job satisfaction is most influenced by positive and democratic school culture.